Variance in Arabic Manuscripts. Arabic Didactic Poems from the Eleventh to the Seventeenth Centuries - Analysis of Textual Variance and Its Control in the Manuscripts - Sobieroj, Florian (Studies in Manuscript Cultures, 2016)
In Arabic and Islamic studies, the subject of variance in general and that of textual variation in particular has not been investigated exhaustively so far. In the present book the variation in texts of the "closed transmission" will be studied, focusing on a small corpus of didactic and model poems, with a view to establishing what degree of text stability and change was allowed by the medium manuscript. Categories of variance (relating to work-titles, text, number of verses and their sequence, page-layout, context) and the means of controlling them in the manuscripts of the poems are identified and detailed descriptions of the copies are given. The monograph also includes a presentation of some major traits of the cultural background to the study of Arabic didactic poetry and of its dissemination in which memorization has played a crucial role. The intended readers,editors and other users of manuscripts, are helped to acquaint themselves with the methods employed in the manuscripts to control variation and they are given an overview of the large spectrum of Arabic didactic poetry and of its place in the traditional culture of learning in Islamicate societies.